High expression of formin-2 can promote ovarian cancer chemoresistance via immunosuppressive macrophages - Shuo Feng; Yaping Wang; Ran Ren; Xiaotong Wang; Lu Han (Functional & Integrative Genomics, 2026)

Botulinum toxin injection combined with rehabilitation training for peroneal spastic flatfoot: A pilot case series - Ran Zhang; Yaping Chen; Xiuying Huang; Yuxin Tian; Lu Wang (Toxicon, 2026)

Anomalous thermally enhanced output and ion-exchange repairability of flame-retardant waste cotton textile-based triboelectric nanogenerators - Kun Zhao; Yaping Liu; Li Chen; Mengdan Shen; Xuefeng Lu; Yuandong Li; Yong Wang; Kewei Zhang (Chemical Engineering Journal, 2026)

Performance optimization and application advances of cellulose-based triboelectric materials for high-humidity environments - Yakun Mou; Yuhang Qiu; Mingyang Li; Yaping Zeng; Yanniu Xu; Dengjun Lu (Carbohydrate Polymers, 2026)

Synergistic enhancement of sodium storage in bamboo-derived hard carbon via Ni nanoparticle incorporation and P-doping - Wanquan Liu; Liu Wang; Wenjing Lu; Yong Cheng; Yu Chen; Enze Ren; Zhenyao Wang; Jing Wu; Xinhui Li; Yaping Zeng (Biomass and Bioenergy, 2026)

Systematic review on atmospheric pollution during highway construction through multiple monitoring data-source - Shanqian Huang; Xinjun Wang; Chunying Lu; Jinsheng Fu; Yaping Kong (Transportation Research Part D: Transport and Environment, 2026)

LC-MS/MS analysis of polar pesticides in mango: enantiomers, docking, and retention mechanisms - Hao Yang; Yue Geng; Shu Lin; Yawei Xu; Lu Wang; Yi Peng; Yaping Xu; Xiaowei Liu; Zeying He (Food Chemistry, 2026)

Early nut exploitation and its potential for the adaptation of hunter-gatherers to climate change during the LGM in southern China - Qingjiang Yang; Keliang Zhao; Lingxia Zhao; Xinying Zhou; Lili Lu; Yaping Zhang; Lizhao Zhang; Jian Wang; Xinyi Lu; Xiaoqiang Li (Science China Earth Sciences, 2026)

Changes of soil nematode communities affect the soil labile phosphorus under nitrogen addition in Pinus taiwanensis forests - Chenxing Lian; Qiufang Zhang; Xiaoqing Zhang; Mengli Liu; Quanxin Zeng; Yaping Lin; Jiaohong Lu; Hao Sun; Huizhi Pi; Mengxiao Ren; Xiaochun Yuan; Juyan Cui; et al. (Applied Soil Ecology, 2026)

Grass carp TMEM33 promotes GCRV replication by targeting MAVS for degradation and suppressing host antiviral immune response - Qian Wang; Zichao Peng; Rong Deng; Yongming Li; Zuoyan Zhu; Yaping Wang; Libo He; Jing Lu (Marine Life Science & Technology, 2026)

UiO-66 porous liquids with synergistic catalytic effects for promoting efficient CO2 conversion - Yaru Lu; Ruyu Bai; Dechao Wang; Yangyang Xin; Weirui Zhang; Fangfang Su; Zheng Dong; Wendi Fan; Yating Zhang; Fangli Yu; Xin Li; Yingying Zhou; et al. (Chemical Engineering Journal, 2026)

Targeting the gut-liver axis with dietary polyphenols to ameliorate metabolic dysfunction-associated steatotic liver disease: advances in molecular mechanisms - Zuomin Hu; Zeyu He; Yuyan Wang; Zhongxing Chu; Yaping Zhou; Wen Li; Jun Lu; Qinlu Lin; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2026)

Characterization of Neomegalonema-dominated granulation in aerobic granules bioreactor: Evidence for stable filamentous granulation and quorum sensing-related activities - Lili Sun; Hanquan Wen; Lu Ding; Chao Qin; Mingxi Chen; Shike She; Xinchao Zhu; Jian Wang; Zengyang He; Yaping Zhang; Zhiqiang Xu; Quan Shu; et al. (Environmental Research, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Anti-inflammatory Effects of Membrane Vesicles from Eubacterium rectale via the NLRP3 Signal Pathway - Hongxia Zhang; Yanan Zhao; Dengfu Li; Haixia Li; Zhu Wang; Lu Zhang; Huafeng Niu; Yuchen Huang; Chenchong Zhao; Yaping Jin; Dong Zhou (Probiotics and Antimicrobial Proteins, 2025)

Enhancing the identification of malonylation sites using AlphaFold2 and ensemble learning - Linlin Xu; Yuting Qian; Jiayi Yang; Xiaowei Xu; Zhiqiang Li; Yanhan Wang; Enhui Lv; Xingxing Kang; Hongwei Zhang; Yaping Lu; Fei Wang; Xin Liu (Molecular Diversity, 2025)

Corrigendum to “The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans” [Plant Sci. 357 (2025), 112539] - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Corrigendum to “The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans“ [Plant Sci. 357 (2025) 112539] - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

Robust topology optimization of multi-material structure with load uncertainty based on element-free Galerkin method - Jianping Zhang; Tao Chen; Jiahong Chen; Xuemei Peng; Yaping Zhao; Haishan Lu; Dabing Zhang (Engineering Structures, 2025)

Assessment for the wildlife crossing structures along the Qinghai-Tibet railway - Abudusaimaiti Maierdiyali; Yun Wang; Jiding Chen; Runsheng Li; Mei Luo; Xueyang Li; Yangang Yang; Shuangcheng Tao; Yaping Kong; Hao Wang; Zhi Lu (Transportation Research Part D: Transport and Environment, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Research progress on properties and applications of triboelectric nanogenerators based on cellulosic triboelectric aerogels - Yuhang Qiu; Yakun Mou; Xunxiao Wu; Yaping Zeng; Yanniu Xu; Mingyang Li; Dengjun Lu (Chemical Engineering Journal, 2025)

The role of ribosomal protein StRPS5 in mediating resistance of Solanum tuberosum plants to Phytophthora infestans - Jing Liu; Yaping Hu; Xiaoqing Lu; Jifen Xu; Hongyang Wang; Wei Tang; Canhui Li (Plant Science, 2025)

The interspecies relationships among the wildlife crossing structures of the Qinghai-Tibet Railway - Abudusaimaiti Maierdiyali; Yun Wang; Jiding Chen; Runsheng Li; Yangang Yang; Shuangcheng Tao; Yaping Kong; Zhi Lu (Journal for Nature Conservation, 2025)

Enhanced nitrogen and phosphorus removal from actual domestic sewage using a novel ecological AAO process integrated with natural zeolite and vegetation - Zhiqiang Wang; Hua Chen; Jian Sun; Xingwen Lu; Yao He; Yujie Wang; Yaping Zhang; Renli Liang (Journal of Water Process Engineering, 2025)

Temporal and spatial changes of ungulate activity before and after the construction of the Qinghai-Tibet railway in Hoh Xil, China - Abudusaimaiti Maierdiyali; Yun Wang; Yangang Yang; Shuangcheng Tao; Yaping Kong; Jiding Chen; Xin Yang; Basanglamao; Hao Wang; Zhi Lu (Journal of Transport Geography, 2025)

Enzymatic degradation of mycotoxin patulin by a short-chain dehydrogenase/reductase from Bacillus subtilis and its application in apple juice - Jiafeng Niu; Bin Ma; Juan Shen; Hao Zhu; Yaping Lu; Zhaoxin Lu; Fengxia Lu; Ping Zhu (Food Microbiology, 2025)

Online SFE-SFC-MS/MS analysis of pyraclostrobin and chiral mefentrifluconazole residues in mango and mango juice - Hao Yang; Yue Geng; Shu Lin; Lu Wang; Yi Peng; Yaping Xu; Wei Jing; Jing Wei; Zeying He; Xiaowei Liu (Food Chemistry, 2025)

Analysis of Common Genetic Variation of Anxiety Disorders in Essential Tremor - Yaping Yan; Lanxiao Cao; Luyan Gu; Congying Xu; Jinyu Lu; Dayao Lv; Jun Tian; Xinzhen Yin; Jiali Pu; Baorong Zhang; Guohua Zhao (Journal of Molecular Neuroscience, 2025)

Peanut–cotton intercropping to enhance soil ecosystem multifunctionality: Roles of microbial keystone taxa, assembly processes, and C-cycling profiles - Shijie Zhang; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Shiwu Xiong; Beifang Yang; Xiaoyu Zhi; Minghua Xin; Yahui Jiao; Xiao-Fei Li; Yabing Li; et al. (Agriculture, Ecosystems & Environment, 2025)

Development of the CMA-ChemRA: China Regional Weakly Coupled Chemical-Weather Reanalysis System with product since 2007 - Tao Zhang; Zijiang Zhou; Zhisen Zhang; Junting Zhong; Zhiquan Liu; Xiaoye Zhang; Wenhui Xu; Lipeng Jiang; Jie Liao; Yaping Ma; Yike Zhou; Huiying Wang; et al. (Science of The Total Environment, 2024)

One-step synthesis of iron and carbon-quantum-dot co-decorated graphitic carbon nitride photocatalysts for carbamazepine degradation - Xiaoli Liu; Yaping Wang; Yutao Xie; Tiefeng Xu; Yan Gu; Wangyang Lu (Journal of Environmental Chemical Engineering, 2024)

Multi-functional graphene aerogels/epoxy resin composites with Janus structure for enhanced electromagnetic interference shielding - Zhongjie He; Xiaoqian Li; Weirui Zhang; Xiaoyu Cheng; Mingzhong Wang; Wenjing Lu; Dongdong Yao; Yaping Zheng; Jiahe Liang (Chemical Engineering Journal, 2024)

Early-onset familial essential tremor is associated with nucleotide expansions of spinocerebellar ataxia in China - Zhilin Zheng; Zeyu Zhu; Jiali Pu; Chen Zhou; Lanxiao Cao; Dayao Lv; Jinyu Lu; Gaohua Zhao; Yanxing Chen; Jun Tian; Xinzhen Yin; Baorong Zhang; et al. (Molecular Biology Reports, 2024)

Foreign directors and corporate social responsibility reporting in China: the moderating role of institutional pressures - Weizhang Sun; Yi Lu; Yifei Zhang; Yaping Wang; Zhizhong Xue (Environment, Development and Sustainability, 2024)

One-step hydrothermal synthesis of nitrogen-doped carbon-quantum-dots for detection and efficient removal of high-concentrations nicotine from tobacco wastewater under visible light - Xiaoli Liu; Yaping Wang; Yan Gu; Wangyang Lu (Chemical Engineering Journal, 2024)

Angelica sinensis polysaccharides promote extramedullary stress erythropoiesis via ameliorating splenic glycolysis and EPO/STAT5 signaling-regulated macrophages - Nianci Sun; Ziling Wang; Honghui Jiang; Biyao Wang; Kunhang Du; Caihong Huang; Cheng Wang; Ting Yang; Yaping Wang; Yafei Liu; Lu Wang (Journal of Molecular Histology, 2024)

Effect of Fe2+-activated persulfate combined with biodegradation in removing gasoline BTX from karst groundwater: A box-column experimental study - Yaping Jiang; Renqian Lu; Yudao Chen; Ritian Deng; Xu Deng (Environmental Science and Pollution Research, 2024)

Neg1 overexpression in Trichoderma harzianum T4 enhanced its ability to produce spores and antagonistic activity against phytopathogenic fungi - Jingwen Liu; Yaping Wang; Shouquan Lu; Xiaoxu Liu; Henan Zhang; Wei Wang (Archives of Microbiology, 2024)

Molecular Cloning and Characterization of Scavenger Receptor Class B Type 1 in Grass Carp (Ctenopharyngodon idellus) and Its Expression Profile following Grass Carp Reovirus Challenge - Yang Zhang; Jiayuan Shi; Yuntao Lu; Qing Luo; Pengfei Chu; Rong Huang; Kunci Chen; Jian Zhao; Yaping Wang; Mi Ou (Fishes, 2024)
As a member of the pattern recognition receptor (PRR) class, scavenger receptor class B type 1 (SRB1) plays a key role in innate immunity. Grass carp (Ctenopharyngodon idellus) ranks among the most extensively cultivated freshwater aquaculture species in China. However, little is known about the function of SRB1 in C. idellus. In this research study, a SRB1 gene was identified in C. idellus, named CiSRB1. The full-length cDNA of CiSRB1 is 2486 bp long, with an open reading frame (ORF) of 2486 bp encoding a 497 amino acid (aa) protein containing a conserved CD36 domain. The identified genomic DNA length of CiSRB1 is 20,042 bp, including 12 exons and 11 introns. The predictive analysis of protein interactions revealed that CiSRB1 could interact with the outer capsid proteins of typical GCRV strains. The tissue distribution of CiSRB1 exhibited age-dependent characteristics. CiSRB1 displayed the highest expression in the intestines and moderate levels in muscle, spleen, liver, and brain of one-year-old grass carp while maintaining relatively low levels in three-year-old grass carp. Following grass carp reovirus (GCRV) infection, notable upregulation of CiSRB1 transcripts was observed in major immune tissues (gills, intestines, spleen, and liver). Furthermore, significant differences were found between one-year-old and three-year-old grass carp, with lower CiSRB1 expression levels being detected in the older group. Additionally, a distinct response to GCRV infection was observed in one-year-old and three-year-old grass carp. It was found that one-year-old individuals had a mortality rate of up to 84% 6 days post-infection (dpi), whereas all three-year-old counterparts survived after GCRV infection. The analysis of GCRV copy numbers across tissues revealed substantially higher levels in one-year-old grass carp compared with their older counterparts, confirming the existence of age-dependent susceptibility to GCRV infection in grass carp. Combined with these results, it was speculated that the decline in cell-surface CiSRB1 expression with age may impede reovirus binding to host cells, potentially explaining why older grass carp demonstrated enhanced resistance to GCRV infection. This observation accentuates the importance of CiSRB1 in the context of GCRV infection and provides insights into age-dependent susceptibility to reovirus.

Recalcitrant components accumulation in dissolved organic matter decreases microbial metabolic quotient of red soil under long-term manuring - Xiao Yang; Shuai Zhang; Dong Wu; Yaping Huang; Lu Zhang; Kailou Liu; Huiqiao Wu; Shengli Guo; Wenju Zhang (Science of The Total Environment, 2024)

Comprehensive comparison of integrated fixed-film activated sludge (IFAS) and AAO activated sludge methods: Influence of different operational parameters - Zihua Lan; Yaping Zhang; Renli Liang; Zhiqiang Wang; Jian Sun; Xingwen Lu; Yao He; Yujie Wang (Chemosphere, 2024)

Spartina alterniflora invasion benefits blue carbon sequestration in China - Jingfan Zhang; Dehua Mao; Jihua Liu; Yaping Chen; Matthew Kirwan; Christian Sanders; Jinge Zhou; Zhe Lu; Guoming Qin; Xingyun Huang; Hui Li; Hengqi Yan; et al. (Science Bulletin, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Functional characterization of polyol/monosaccharide transporter 1 in Lotus japonicus - Leru Liu; Shaoming Xu; Lu Tian; Xuelian Qin; Guojiang Wu; Huawu Jiang; Yaping Chen (Journal of Plant Physiology, 2024)

Reproductive hormones, organophosphate esters and semen quality: Exploring associations and mediation effects among men from an infertility clinic - Yaping Li; Zhiyi Zheng; Dan Luo; Chong Liu; Sijie Yang; Yingjun Chen; Qian Hu; Wenqing Lu; Yixin Wang; Surong Mei (Environmental Research, 2024)

Purification and characterization of a glycoprotein from Sipunculus nudus and its immune-enhancing activity to RAW 264.7 macrophages - Xuli Lu; Yaping Dai; Shengtao Yang; Tengfei Fu; Yunxia He; Fanke Zeng; Tinghui Chen; Yupo Cao; Ruyi Li; Jihua Li; Wei Zhou (Food Research International, 2023)

Unprecedented early summer warming recorded in tree rings on the central eastern Tibetan Plateau over the past three centuries - Jiangfeng Shi; Hui Wang; Jinbao Li; Shiyuan Shi; Jiarui Xu; Yaping Zhang; Huayu Lu (Climate Dynamics, 2023)

Cytotoxic 4-phenylcoumarins from the flowering buds of Mesua ferrea - Xiya Chen; Zhiying Liu; Bi Zhong; Mengjie Zhu; Han Yao; Xiaojie Chen; Yongchao Lu; Shuyun Wang; Yaping Guo (Natural Product Research, 2023)

Characteristics and mechanism of phosphate removal by lanthanum modified bentonite in the presence of dissolved organic matter - Mingxin Zhang; Yaping Zhang; Xi Chen; Jian Sun; Xingwen Lu; Yao He; Yujie Wang (Chemosphere, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Soybean phenological changes in response to climate warming in three northeastern provinces of China - Minghua Xin; Zhenggui Zhang; Yingchun Han; Lu Feng; Yaping Lei; Xiaofei Li; Fengqi Wu; Jian Wang; Zhanbiao Wang; Yabing Li (Field Crops Research, 2023)

Putrescine (1,4-Diaminobutane) enhances antifungal activity in postharvest mango fruit against Colletotrichum gloeosporioides through direct fungicidal and induced resistance mechanisms - Yaping Song; Yanfang Ren; Yuhao Xue; Dandan Lu; Tengyu Yan; Junyu He (Pesticide Biochemistry and Physiology, 2023)

A step closer to real practice: Integrated tandem photocatalysis-biofilm process towards degradation of crude oil - Xin Hu; Yaping Pan; Shanshan Zhao; Feifei Zhang; Fengshu Li; Zhe Li; Haoshuai Li; Yiming Li; Jinren Lu; Xiaolong Yang; Mutai Bao (Journal of Environmental Management, 2023)

Scalable production of polyamide-6/graphene composites with enhanced electromagnetic shielding and thermal conductivity - Rahul Navik; Huijun Tan; Hao Zhang; Zhiyuan Liu; Qixuan Xiang; Liyun Shi; Shiming Lu; Yaping Zhao (Chemical Engineering Journal, 2023)

Assessing Spatio-Temporal Variability of Soil Phosphorus in Different Cotton-Based Cropping Systems Using Geo-Statistics - Li Teng; Xiong Shiwu; Wang Zhanbao; Li Xiaofei; Han Yingchun; Wang Guoping; Lei Yaping; Feng Lu; Yang Beifang; Zhi Xiaoyu; Fan Zhengyi; Li Yabing (Journal of Soil Science and Plant Nutrition, 2023)

One-step preparation of magnetic N-doped sodium alginate–based porous carbon and efficient adsorption of bisphenol A - Yaping Xie; Guoxing Du; Jiaju Pang; Linghan Kong; Linguo Lu (Environmental Science and Pollution Research, 2023)

Optimizing plant type structure to adjust the temporal and spatial distribution of water consumption and promote the growth and yield formation of cotton - Yaru Wang; Jiale Chen; Fengqi Wu; Beifang Yang; Yingchun Han; Lu Feng; Zhanbiao Wang; Xiaofei Li; Yaping Lei; Shiwu Xiong; Guoping Wang; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Uncovering the dynamic evolution of microbes and n-alkanes: Insights from the Kuroshio Extension in the Northwest Pacific Ocean - Xin Hu; Xinping Wang; Shanshan Zhao; Lixin Cao; Yaping Pan; Fujuan Li; Fengshu Li; Jinren Lu; Yiming Li; Guodong Song; Honghai Zhang; Peiyan Sun; et al. (Science of The Total Environment, 2023)

In situ confined growth of g-C3N4/pigment compound catalyst in porous diatomite for enhancing photocatalytic nicotine elimination and bacterial inactivation - Junting Gao; Zhijing Wu; Yaping Wang; Yunjin Zhong; Feng Gao; Wenxing Chen; Wangyang Lu (Journal of Environmental Chemical Engineering, 2023)

A mechanically soft-tissue-like organohydrogel with multi-functionalities for sensitive soft ionotronics - Shuxiang Liu; Yuping Chen; Jin Feng; Junjie Peng; Yaping Zhou; Yang Zhao; Yongpeng Zhao; Zhiwei Lu; Mengmeng Sun; Chun Wu; Haipeng Hu; Hanbing Rao; et al. (Chemical Engineering Journal, 2023)

The nitrogen footprint and reactive nitrogen reduction potential of cotton production in China - Weibin Huang; Fengqi Wu; Zhenggui Zhang; Yongming Meng; Jian Wang; Qinqin Li; Yingchun Han; Lu Feng; Xiaofei Li; Guoping Wang; Yaping Lei; Zhengyi Fan; et al. (Journal of Cleaner Production, 2023)

Association Analysis of 27 Single Nucleotide Polymorphisms in a Chinese Population with Essential Tremor - Lanxiao Cao; Luyan Gu; Jiali Pu; Dayao Lv; Jun Tian; Xinzhen Yin; Ting Gao; Zhe Song; Jinyu Lu; Gaohua Zhao; Baorong Zhang; Yaping Yan; et al. (Journal of Molecular Neuroscience, 2023)

Chronic toxicity of broflanilide in Daphnia magna: changes in molting, behavior, and gene expression - Kai Wang; Yaping Liang; Manman Duan; Wunan Che; Lu He (Environmental Science and Pollution Research, 2023)

Urinary concentrations of organophosphate esters in relation to semen quality: A cross-sectional study - Yaping Li; Dan Luo; Xiaoya Zhao; Han Wang; Zhiyi Zheng; Jun Liu; Chong Liu; Hui Wang; Yingjun Chen; Yinzhu Shang; Wenqing Lu; Surong Mei; et al. (Science of The Total Environment, 2023)

Climate warming accelerates cotton growth while cultivar shifts extend the growth period - Wanrui Han; Shengli Liu; Yaping Lei; Yongjiang Zhang; Yingchun Han; Guoping Wang; Lu Feng; Xiaofei Li; Yabing Li; Zhanbiao Wang (Field Crops Research, 2023)

TCR repertoire landscape reveals macrophage-mediated clone deletion in endotoxin tolerance - Juanjuan Zhao; Li Jia; YiJing Tao; Xu Zhao; Jing Yang; Yanxin Lu; Yaping Yan; Ling Mao; Lin Hu; Jia Lu; MengMeng Guo; Chao Chen; et al. (Inflammation Research, 2023)
Background Endotoxin tolerance (ET) is a protective mechanism in the process of sepsis, septic shock, and their sequelae including uncontrolled inflammation. Accumulating evidence has shown that peripheral T cells contribute to the induction of ET. However, what and how T-cell development contributes to ET inductions remain unclear. Methods Mice were intraperitoneally injected with LPS at a concentration of 5 mg/kg to establish an LPS tolerance model and were divided into two groups: a group examined 72 h after LPS injection (72-h group) and a group examined 8 days after LPS injection (8-day group). Injection of PBS was used as a control. We performed high-throughput sequencing to analyze the characteristics and changes of CD4 + SP TCR β CDR3 repertoires with respect to V direct to J rearrangement during the ET induction. Moreover, the proportion and proliferation, as well as surface molecules such as CD80 and CD86, of F4/80 + macrophages were analyzed using FCM. Furthermore, ACT assay was designed and administered by the tail vein into murine LPS-induced mouse model to evaluate the role of F4/80 + macrophages on the development of CD4 + SP thymocytes in ET condition. Results We found that the frequency and characteristics of the TCR β chain CDR3 changed obviously under condition of ET, indicating the occurrence of TCR rearrangement and thymocyte diversification. Moreover, the absolute numbers of F4/80 + macrophages, but not other APCs, were increased in thymic medulla at 72-h group, accompanied by the elevated function-related molecules of F4/80 + macrophages. Furthermore, adoptively transferred OVA 332-339 peptide-loaded macrophages into Rag-1 −/− mice induced the clone deletion of OVA-specific CD4 + SP, thereby ameliorating the pathology in lung tissue in LPS challenge. Conclusions These data reveal that the frequency and characteristics of the TCR β chain CDR3 undergo dynamic programming under conditions of LPS tolerance. Furthermore, the peripheral macrophages may be a key factor which carry peripheral antigen to thymic medulla and affect the negative selection of T-cell population, thereby contributing to the formation of ET. These results suggest that the clone selection in thymus in ET may confer protection against microbial sepsis.

Gastrodin ameliorates exercise-induced fatigue via modulating Nrf2 pathway and inhibiting inflammation in mice - Yaping Zhou; Qi Wu; Wen Yu; Fan Ye; Yunyun Cao; Otobong D. Akan; Xiuxiu Wu; Tiantian Xie; Han Lu; Fuliang Cao; Feijun Luo; Qinlu Lin (Food Bioscience, 2023)

Orychophragmus violaceus/cotton relay intercropping with reduced N application maintains or improves crop productivity and soil carbon and nitrogen fractions - Zhenggui Zhang; Jian Wang; Shiwu Xiong; Weibin Huang; Xiaofei Li; Minghua Xin; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Beifang Yang; Yabing Li; et al. (Field Crops Research, 2023)

Quantitative evaluation of variation and driving factors of the regional water footprint for cotton production in China - Qinqin Li; Weibin Huang; Jian Wang; Zhenggui Zhang; Yabing Li; Yingchun Han; Lu Feng; Xiaofei Li; Beifang Yang; Guoping Wang; Yaping Lei; Shiwu Xiong; et al. (Sustainable Production and Consumption, 2023)

Fabrication and characterization of l-ascorbyl palmitate and phospholipid-based hybrid liposomes and their impacts on the stability of loaded hydrophobic polyphenols - Mianhong Chen; Ruyi Li; Xuli Lu; Yaping Dai; Tinghui Chen; Yuhang Xing; Lu Xue; Zhihao Duan; Wei Zhou; Jihua Li (Food Chemistry, 2023)

Angelica sinensis polysaccharides prevents hematopoietic regression in D-Galactose-Induced aging model via attenuation of oxidative stress in hematopoietic microenvironment - Pengwei Jing; Xiaoying Song; Lirong Xiong; Biyao Wang; Yaping Wang; Lu Wang (Molecular Biology Reports, 2023)

Dual-objective modeling and optimization of a low-carbon waste-classified collection problem - Xulong Lu; Xujin Pu; Hongfeng Wang; Yaping Fu (Environmental Science and Pollution Research, 2022)

Correction to: Alpinia officinarum mediated copper oxide nanoparticles: synthesis and its antifungal activity against Colletotrichum gloeosporioides - Chunmei Hu; Wenjia Zhu; Ying Lu; Yanfang Ren; Jinyu Gu; Yaping Song; Junyu He (Environmental Science and Pollution Research, 2022)

Alpinia officinarum mediated copper oxide nanoparticles: synthesis and its antifungal activity against Colletotrichum gloeosporioides - Chunmei Hu; Wenjia Zhu; Ying Lu; Yanfang Ren; Jinyu Gu; Yaping Song; Junyu He (Environmental Science and Pollution Research, 2022)

The structure, characterization and dual-activity of exopolysaccharide produced by Bacillus enclensis AP-4 from deep-sea sediments - Xin Hu; Fengshu Li; Xiuli Zhang; Yaping Pan; Jinren Lu; Yiming Li; Mutai Bao (Frontiers in Marine Science, 2022)
In recent years, the exopolysaccharide (EPS) produced by deep-sea bacteria has attracted the interest of various researchers. In the present study, we have explored the properties and structure of a novel exopolysaccharide (called BPS) produced by Bacillus enclensis AP-4 from deep-sea sediments. The maximum yield of BPS was 4.23 ± 0.17 g L −1 in a 2216E modified medium. 1 H NMR studies of the purified BPS displayed α and β-configuration sugar residues, including mannose, glucosamine, glucose, galactose, and xylose in a molar ratio of 1.00: 0.09: 0.04: 0.09: 0.07. BPS showed a molecular weight of 23,434 Da and was abundant in hydroxyl and amino residues. In addition, BPS exhibited a rod-like structure with a rough surface and was dominated by C, N, and O elements. The exopolysaccharide demonstrated remarkable thermal stability, high degradation temperature, and excellent emulsification capacity compared to most reported exopolysaccharides. Moreover, BPS displayed better quenching activities against the four radicals, which provided favorable protection for the strain. Finally, the freezing experiment investigated the cryoprotective effect of BPS on E. coli and S. aureus . BPS effectively improved the cell survival ratio and maintained the activity of Na + /K + -ATPase, which facilitates culture preservation. To the best of our knowledge, our work is the first report suggesting that marine exopolysaccharide has dual-activity. This work presents the foundation for the analysis of the structure and properties of exopolysaccharides produced by deep-sea bacteria.

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

Development of center pivot irrigation farmlands from 2009 to 2018 in the Mu Us dune field, China: Implication for land use planning - Xiaokang Liu; Zhibao Dong; Yaping Ding; Ruijie Lu; Liyun Liu; Zhiyong Ding; Yijing Li (Journal of Geographical Sciences, 2022)

Gene expression in the microbial consortia of colonial Microcystis aeruginosa ‐a potential buoyant particulate biofilm - Limei Shi; Yuanfeng Cai; Shengling Gao; Daoyan Fang; Yaping Lu; Pengfu Li; Qinglong L. Wu (Environmental Microbiology, 2022)
Microcystis spp., notorious bloom‐forming cyanobacteria, are often present in colony form in eutrophic lakes worldwide. Uncovering the mechanisms underlying Microcystis colony formation and maintenance is vital to controlling the blooms, but it has long been a challenge. Here, bacterial communities and gene expression patterns of colonial and unicellular forms of one non‐axenic strain of Microcystis aeruginosa isolated from Lake Taihu were compared. Evidently, different microbial communities between them were observed through 16S rDNA MiSeq sequencing. Metatranscriptome analyses revealed that transcripts for pathways involved in bacterial biofilm formation, such as biosynthesis of peptidoglycan and arginine by Bacteroidetes , methionine biosynthesis, alginate metabolism, flagellum, and motility, as well as widespread colonization islands by Proteobacteria , were highly enriched in the colonial form. Furthermore, transcripts for nitrogen fixation and denitrification pathways by Proteobacteria that usually occur in biofilms were significantly enriched in the colonial Microcystis . Results revealed that microbes associated with Microcystis colonies play important roles through regulation of biofilm‐related genes in colony formation and maintenance. Moreover, Microcystis colony represents a potential ‘buoyant particulate biofilm’, which is a good model for biofilm studies. The biofilm features of colonial Microcystis throw a new light on management and control of the ubiquitous blooms in eutrophic waters.

A Significant Fluorescent Aptamer Sensor Based on Carbon Dots and Graphene Oxide for Highly Selective Detection of Progesterone - Hanyue Cui; Huan Lu; Jing Yang; Yao Fu; Yan Huang; Li Li; Yaping Ding (Journal of Fluorescence, 2022)

BMAL1 induces colorectal cancer metastasis by stimulating exosome secretion - Pengjuan Dong; Yaping Wang; Yutong Liu; Chunting Zhu; Jiaxin Lin; Ruizhe Qian; Luchun Hua; Chao Lu (Molecular Biology Reports, 2022)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

The emerging role of circular RNAs in cardiovascular diseases - Yuejia Ding; Chunmiao Lu; Wanqin Zhang; Yuan Wang; Yanyang Li; Yaping Zhu; Shichao Lv; Junping Zhang (Journal of Physiology and Biochemistry, 2021)

Study of the geostatistical grid maths operation method of quantifying water movement in soil layers of a cotton field * - Liyuan Liu; Fangfang Xing; Yabing Li; Yingchun Han; Zhanbiao Wang; Xiaoyu Zhi; Guoping Wang; Lu Feng; Beifang Yang; Yaping Lei; Zhengyi Fan; Wenli Du (Irrigation and Drainage, 2020)
The precise quantification of water movement in different field soil layers is important for variable‐rate irrigation and fertilization. To this end, a field experiment based on a geostatistical approach was conducted in southern Anyang, Henan, China, to examine soil water movement in a cotton field with drip irrigation by measuring the soil water content (SWC) data on a regular 100 × 80 cm grid. The result shows that the temporal and spatial variation of soil moisture decreased with the increase of soil depth at different points, and apparent spatial heterogeneity was observed under different soil conditions through a semivariogram analysis. The variation of soil moisture at different soil profiles was affected by the cotton plants and drip lines in non‐irrigation and irrigation periods respectively. The level of the change at 20 cm was more than 70 cm in the horizontal direction in the two periods, however the degree of change at 40 cm in the irrigation period was more than 70 cm in the vertical direction, while contrary results were shown in the non‐irrigation period. Moreover, the results indicated that the trapezoidal rule could be applied to quantify the volume of water movement precisely.

Application of next-generation sequencing to screen for pathogenic mutations in 123 unrelated Chinese patients with Marfan syndrome or a related disease - Jiacheng Li; Chaoxia Lu; Wei Wu; Yaping Liu; Rongrong Wang; Nuo Si; Xiaolu Meng; Shuyang Zhang; Xue Zhang (Science China Life Sciences, 2019)

Comparative genomics for non-O1/O139 Vibrio cholerae isolates recovered from the Yangtze River Estuary versus V. cholerae representative isolates from serogroup O1 - Li Gong; Pan Yu; Huajun Zheng; Wenyi Gu; Wei He; Yadong Tang; Yaping Wang; Yue Dong; Xu Peng; Qunxin She; Lu Xie; Lanming Chen (Molecular Genetics and Genomics, 2019)

Elucidating the molecular mechanism of the inhibitory effect of epigallocatechin-3-gallate on Microcystis aeruginosa - Jin Wang; Chen Dai; Xiaoqian Zhang; Yaping Lu (Journal of Applied Phycology, 2018)

Stocks and dynamics of particulate and dissolved organic matter in a large, shallow eutrophic lake (Taihu, China) with dense cyanobacterial blooms - Limei Shi; Yaxin Huang; Yaping Lu; Feizhou Chen; Min Zhang; Yang Yu; Fanxiang Kong (Journal of Oceanology and Limnology, 2018)

Bacterial community temporal dynamics and disease-related variations in the seawater of Pyropia (laver) seedling pools - Xiangyu Guan; Wei Zhou; Chuanming Hu; Miaoxian Zhu; Yaping Ding; Shanshan Gai; Xiaoxuan Zheng; Jianyi Zhu; Qinqin Lu (Journal of Applied Phycology, 2018)

Brg1 inhibits E-cadherin expression in lung epithelial cells and disrupts epithelial integrity - Ting Wang; Wenjing Zou; Chao Niu; Fengxia Ding; Yaping Wang; Shuang Cai; Hua Zhu; Daiyin Tian; Jihong Dai; Enmei Liu; Qing Lu; Zhou Fu; et al. (Journal of Molecular Medicine, 2017)

Ginsenoside Rg1 protects human umbilical cord blood-derived stromal cells against tert-Butyl hydroperoxide-induced apoptosis through Akt–FoxO3a–Bim signaling pathway - Ying Liu; Long Yi; Lu Wang; Linbo Chen; Xiongbin Chen; Yaping Wang (Molecular and Cellular Biochemistry, 2016)

Effects of Land Use Change on Phosphorus Levels in Surface Waters—a Case Study of a Watershed Strongly Influenced by Agriculture - Bin Zhou; Yaping Xu; Rolf D. Vogt; Xueqiang Lu; Xuemei Li; Xiaowen Deng; Ang Yue; Liang Zhu (Water, Air, & Soil Pollution, 2016)

A Fluorescent Switch Sensor for Glutathione Detection Based on Mn-doped CdTe Quantum Dots - Methyl Viologen Nanohybrids - Lurong Yu; Li Li; Yaping Ding; Yaxiang Lu (Journal of Fluorescence, 2016)

Inhibition of the growth of cyanobacteria during the recruitment stage in Lake Taihu - Yaping Lu; Jin Wang; Xiaoqian Zhang; Fanxiang Kong (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

A Simple Fluorescence Quenching Method for the Determination of Vanillin Using TGA-capped CdTe/ZnS Nanoparticles as Probes - Li Li; Qiaolin Zhang; Yaping Ding; Yaxiang Lu; Xiaoyong Cai; Lurong Yu (Journal of Fluorescence, 2015)

FLT3 and CDK4/6 inhibitors: Signaling mechanisms and tumor burden in subcutaneous and orthotopic mouse models of acute myeloid leukemia - Yaping Zhang; Cheng-Pang Hsu; Jian-Feng Lu; Mita Kuchimanchi; Yu-Nien Sun; Ji Ma; Guifen Xu; Yilong Zhang; Yang Xu; Margaret Weidner; Justin Huard; David Z. D’Argenio (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Hepatocyte Nuclear Factor 4 Alpha and Farnesoid X Receptor Co-regulates Gene Transcription in Mouse Livers on a Genome-Wide Scale - Ann M. Thomas; Steve N. Hart; Guodong Li; Hong Lu; Yaping Fang; Jianwen Fang; Xiao-bo Zhong; Grace L. Guo (Pharmaceutical Research, 2013)

Inhibition of Camellia sinensis (L.) O. Kuntze on Microcystis aeruginosa and isolation of the inhibition factors - Yaping Lu; Jin Wang; Yang Yu; Wen Su; Fanxiang Kong (Biotechnology Letters, 2013)

Effect of chlorogenic acid on LPS-induced proinflammatory signaling in hepatic stellate cells - Haitao Shi; Lei Dong; Xiaoyan Dang; Yaping Liu; Jiong Jiang; Yan Wang; Xiaolan Lu; Xiaoyan Guo (Inflammation Research, 2013)

Modulation of hsa-miR-26b levels following adipokine stimulation - Guangfeng Xu; Chenbo Ji; Chunmei Shi; Hailong Fu; Lingling Zhu; Lu Zhu; Lulian Xu; Ling Chen; Yueying Feng; Yaping Zhao; Xirong Guo (Molecular Biology Reports, 2013)

Determination of Paracetamol Based on its Quenching Effect on the Photoluminescence of CdTe Fluorescence Probes - Li Li; Yaxiang Lu; Yaping Ding; Yu Cheng; Wanchen Xu; Fenfen Zhang (Journal of Fluorescence, 2012)

A quick isolation method for mutants with high lipid yield in oleaginous yeast - Jufang Wang; Renmin Li; Dong Lu; Shuang Ma; Yaping Yan; Wenjian Li (World Journal of Microbiology and Biotechnology, 2009)

Effects of in utero meso-2,3-dimercaptosuccinic acid with calcium and ascorbic acid on lead-induced fetal development - Fei Yu; Yingjun Liao; Yaping Jin; Yue Zhao; Yahao Ren; Chunwei Lu; Gexin Li; Yanxi Li; Jun Yang (Archives of Toxicology, 2008)

Therapeutic potentials of combined use of DMSA with calcium and ascorbic acid in the treatment of mild to moderately lead intoxicated mice - Yingjun Liao; Jun Zhang; Yaping Jin; Chunwei Lu; Gexin Li; Fei Yu; Xuping Zhi; Li An; Jun Yang (BioMetals, 2008)

Selection of micronutrients used along with DMSA in the treatment of moderately lead intoxicated mice - Yingjun Liao; Fei Yu; Yaping Jin; Chunwei Lu; Gexin Li; Xuping Zhi; Li An; Jun Yang (Archives of Toxicology, 2008)

Multiple origins of Tibetan Y chromosomes - Yaping Qian; Binzhi Qian; Bing Su; Jiankun Yu; Yuehai Ke; Zhengtao Chu; Lei Shi; Daru Lu; Jiayou Chu; Li Jin (Human Genetics, 2000)